Effectiveness of different exercise intensity on muscle strength, balance, and mobility of elderly women - Ghasemabad, Kamran Hosseinzadeh (2023)
This study aimed to investigate the effectiveness of different exercise intensities on muscle strength, dynamic–static balance as well as functional mobility of elderly women in different time periods. Participants in this study were chosen using simple random sampling from Malaysian older women (N=60) aged >65 years old who were randomly divided to the high-intensity training (HIT; n=15) (Mean age of 69.60 ± 3.68); moderate-intensity training (MIT; n=15) (Mean age of 69.27 ± 3.41); low-intensity training (LIT; n=15) (Mean age of 69.27 ± 1.94); and control group (CG; n=15) (Mean age of 68.67 ± 2.38). Experimental research designs were used in the present study. The experimental groups underwent a specific lower body training including leg press, leg extension, leg curl and seated calf raises for 12 weeks, but each group had different intensity. The HIT group did 80-90% of 1RM for 4 to 6 reps, The MIT group did 65-75% for 8-10 reps, and the LIT group did 50- 60% for 12-14 reps, and the control group did not do any physical activity. In this study, seven tests were used for measurement: 5 times sit to stand (5STS) for strength, tandem stand test (TST) and one leg stand (OLS) for static balance, forward reach test (FRT) and lateral reach test (LRT) for dynamic balance, and timed up and go test (TUG) and 6-minute walking test (6MWT) for functional mobility were administered to all participants to measure their changes at week 4, 8, and 12. There were no statistically significant differences in the distributions of all assessments scores for the dependent variables between the treatment groups and control group prior to the intervention. The post-intervention measurements using two-way repeated measures ANCOVA showed significant improvements in lower extremity muscle strength (HIT=19.28%, MIT=10.87%, LIT=6.86%, [p<0.001]), dynamic balance ability by FRT (HIT=36.6%, MIT=22.1%, LIT=12.3%, [p<0.001]), and LRT (HIT=64.4%, MIT=36.3%, LIT=23.3% p < 0.001), static balance by OLS (HIT=18.7%, MIT=14.4%, LIT=6.3%, [p<0.001]), and TST (HIT=76.2%, MIT=44.65%, LIT=30.95%, [p<0.001], and functional mobility by TUG (HIT=23.71%, MIT=18.33%, LIT=9.68%, [p<0.001]), and 6MWT (HIT=13.98%, MIT=11.57%, LIT=6.58%, [p<0.001]). This analysis showed that there was a statistical difference in the means of all the variables between groups (p<0.001) and in the means of all variables in different time points (except on 5STS and OLS tests). Moreover, a statistically significant connection between the intervention and time on all the variables (p<0.001) was also observed. Besides that, the multivariate analysis concluded a significant improvement in static– dynamic balance, and functional mobility. The results suggest that all three different training intensities are beneficial for improving muscle strength, static– dynamic balance, and functional mobility. In addition, HIT is most effective in improving muscle strength, static balance, dynamic balance, and functional mobility after 12 weeks of interventions.